2017
DOI: 10.1007/978-3-319-89935-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Crowd Sensing of Water Level to Improve Flood Forecasting in Small Drainage Areas

Abstract: Flood forecasting is particularly difficult and uncertain for small drainage basins. One reason for this is due to inadequate temporal and spatial hydrological input variables for model-based flood predictions. Incorporating additional information collected by volunteers with the help of their smartphones can improve flood forecasting systems. Data collected in this way is often referred to VGI data (Volunteered Geographic Information data). This paper discusses how this information can be incorporated into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Zabota and Kobal [ 41 ] discuss a new methodology for collecting data on past rockfall events through mobile application to enhance the quality of rockfall risk assessment. Burkard et al [ 42 ] present image-based methods for measuring the water level at small drainage areas with a mobile phone and inbuilt sensors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zabota and Kobal [ 41 ] discuss a new methodology for collecting data on past rockfall events through mobile application to enhance the quality of rockfall risk assessment. Burkard et al [ 42 ] present image-based methods for measuring the water level at small drainage areas with a mobile phone and inbuilt sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Information exchange between citizens is overlooked in this study. Burkard et al [ 42 ] present image-based measurement methods to feed into a conceptual flood prediction system that can be used in rivers. The methods are based on three variants of inclination, reference points, and correspondence points, which are measured using the camera and orientation sensors (accelerometer and gyroscope) of a smartphone.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the severe climate changes experienced in the last few years, flood occurrences increased considerably, and containing their effects requires up-to-date and accurate knowledge of some critical environmental state variables [269]. Some studies have demonstrated that smartphones can estimate important parameters such as water levels, with an accuracy that can even achieve the cm level when the images captured by cameras are fused with the builtin orientation sensors [269,270]. The main drawback resides in the still too-involved operations that are demanded of the volunteers in order to carry out meaningful measurements.…”
Section: Crowdsensing For Marine and Water Monitoringmentioning
confidence: 99%